Enhancing Early Literacy: The Effect of Flashcard-Based Learning Media on Consonant Letter Recognition in Early Childhood Education - Yayah Usriyah; Irfan Fauzi Rahmat; Abdul Muiz Rouf (International Journal of Educational Qualitative Quantitative Research, 2026)
Visual discrimination of letters with similar graphic forms (e.g., b, d, p, q) presents a significant cognitive challenge in early childhood literacy development. This study investigates the effect of flashcard-based learning media on enhancing consonant letter recognition among young learners. Utilizing a Classroom Action Research (CAR) design spanning two iterative cycles, the intervention involved 15 children aged 4–5 years at a purposively selected early childhood education center in Indonesia. Data were gathered through structured observations, semi-structured teacher interviews, and pedagogical documentation. The findings revealed a progressive improvement in children’s letter recognition and visual differentiation capabilities. The mastery rate increased significantly from a baseline of 26.67% in the pre-cycle stage to 53.33% in Cycle I, ultimately achieving 80.00% in Cycle II. The integration of high-contrast, interactive flashcards combined with game-based learning effectively mitigated mirror-letter confusion by reducing cognitive load and enhancing visual retention. Furthermore, the approach stimulated active participation and learning motivation. These results suggest that structured visual media serve as a critical scaffold for early orthographic processing. This study contributes to early childhood pedagogy by providing an empirical framework for addressing specific letter-reversal difficulties through targeted visual stimulation.